Associations of Physical Activity, Kidney Function, Diet, and Inflammatory Markers in High-Risk Type-2 Diabetes With Early-Stage Chronic Kidney Disease (CKD) - Faatihah Niyi-Odumosu (Asian Society of Kinesiology, 2022)
OBJECTIVES Quantitative information and associations of physical activity, kidney function, diet, and inflammation are dearth in high-risk diabetes. Yet could delay type-2 diabetes, late-stage chronic kidney disease (CKD) and could be useful in designing effective interventions. The study aims to quantify the associations of physical activity, kidney function, diet and inflammation in adults with high-risk type-2 diabetes (and early CKD) recruited to a lifestyle education programme. METHODS Baseline, 12-month dietary, accelerometery, and circulating inflammatory markers, Interleukin-6 (IL-6) and C-reactive protein (CRP) data were assessed from 159 (104 male) high-risk diabetes with stage 2 CKD (mean (SD) estimated glomerular filteration rate (eGFR); 77.5(7.6) ml/min/1.73m2, age; 66(6) years, BMI; 31.8(4.2) kg/m2) who were recruited to a lifestyle education programme. Linear regression examined the effects and associations of the outcome measures. RESULTS eGFR decreased by -2.0 (1.7) ml/min/1.73 m2 (P = 0.04) after 12-months, but mean daily steps, moderate to vigorous physical activity (MVPA) levels, intakes of fibre, total and unsaturated fat, and circulating IL-6 and CRP did not change. However, inter-individual responses were highly variable. eGFR correlated positively with baseline IL-6 (r = 0.17, P = 0.02). Unadjusted, there were no associations between change in eGFR (12_0) and change in any of the activity, inflammatory or dietary outcomes. However, the regression models of these outcomes for change in eGFR (12_0) became significant with multiple covariates. CONCLUSION A combination of healthy lifestyle behaviours should be encouraged for a positive effect on future kidney function.